No Protectionist Policy Before and During the Great Recession - Hylke Vandenbussche; Christian Viegelahn (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2011)
This paper evaluates the Eurpean Union's antidumping (AD) policy from 1995-2009 with a special focus on the 2008-9 crisis. Combining product-level data on AD cases with detailed import data, we fail to find clear signs of a major trade policy change since the outbreak of the crisis. Our findings suggest that the EU largely remained on its pre-crisis path of AD policy with an increasing share of products and more industries covered by AD measures. Moreover, EU AD policy has increasingly focused on China and other lower middle income countries as targets. Further findings suggest that the EU is more likely to impose protection against countries and country-industries that are similar in their product mix. Country-product combinations subject to a preferential tariff are also more likely to be targeted. In tfirms of product characteristics, we observe that especially the shares of consumer goods and differentiated goods covered by EU AD measures have increased rapidly, remaining at a relatively high level also during the crisis.The patterns we reveal do not appear to be driven by a few outlying countries but are also similar when considering imports of individual EU member states.
Keywords: F13; F14; F52; G01; 330; Antidumping; crisis; European Union; great recession; product-level data; temporary trade barriers; trade policy; WTO